Neural Correlates of Working Memory Maintenance in Advanced Aging: Evidence From fMRI - Suzuki, Maki; Kawagoe, Toshikazu; Nishiguchi, Shu; Abe, Nobuhito; Otsuka, Yuki; Nakai, Ryusuke; Asano, Kohei; Yamada, Minoru; Yoshikawa, Sakiko; Sekiyama, Kaoru (Frontiers in Aging Neuroscience, 2018)
Working memory-related brain activity is known to be modulated by aging; particularly, older adults demonstrate greater activity than young adults. However, it is still unclear whether the activity increase in older adults is also observed in advanced aging. The present functional magnetic resonance imaging (fMRI) study was designed to clarify the neural correlates of working memory in advanced aging. Further, we set out to investigate in the case that adults of advanced age do show age-related increase in working memory-related activity, what the functional significance of this over-recruitment might be. Two groups of older adults - “young-old” (61-70 years, n = 17) and “old-old” (77-82 years, n = 16) - were scanned while performing a visual working memory task (the n-back task: 0-back and 1-back). Working memory effects (1-back > 0-back) common to both age groups were identified in several regions, including the bilateral dorsolateral prefrontal cortex (DLPFC), the inferior parietal cortex, and the insula. Greater working memory effects in the old-old than in the young-old group were identified in the right caudal DLPFC. These results were replicated when we performed a separate analysis between two age groups with the same level of working memory performance (the young-old vs. a “high-performing” subset of the old-old group). There were no regions where working memory effects were greater in the young-old group than in the old-old group. Importantly, the magnitude of the over-recruitment working memory effects positively correlated with working memory performance in the old-old group, but not in the young-old group. The present findings suggest that cortical over-recruitment occurs in advanced old age, and that increased activity may serve a compensatory function in mediating working memory performance.